Rebel Youths: English-language anarchist periodicals of the Great Depression, 1932–1939. (30th November 2018) - Brodie, Morris
Abstract : This article examines the function of anarchist periodicals in the United States during the Great Depression. Periodicals acted as forums for debate, where ideas were constantly challenged and important theoretical issues were aired. This was both within anarchism and between the wider radical movement. In addition, periodicals were important organisational tools, creating networks that connected activists across the country and helped to build the movement. Young anarchists identified English-language periodicals as vital for breaking through the linguistic barriers erected by the older generation of immigrant anarchists. The new cohort felt that the reluctance of older anarchists to engage in English-language organising was contributing to the stagnation of the movement and produced three periodicals – Vanguard, Spanish Revolution and Challenge – to address the problem. This article shows how these periodicals helped to reform and sustain anarchist militant identities in the U.S. in the 1930s. It highlights the importance of periodical networks in this process, emphasising their social and cultural value in addition to their political and financial significance. Although all the periodicals had folded by the end of 1939, they left an important legacy for the movement and provided an introduction to anarchist organising for a fresh cadre of activists.